Peran Orang Tua Berhubungan dengan Perilaku Seksual Pra Nikah Remaja di SMKN 1 Sedayu - Diah Suci Haryani; Wahyuningsih Wahyuningsih; Kayat Haryani (Alma Ata University Press, 2015)
Adolescent begins with puberty, that time of the occurrence of physical changes include and physiological functions such as the maturity of the sexual organs. The role of parents is very important to educate, supervise, give an idea how to solve the problem with being a role model and set a good example for adolescent, but it is rarely done by parents because of the background of the parents and the busyness of parents. The purpose of this study was to knowing relationship between role of parents with pre-marital behavior of adolescent in SMKN 1 Sedayu. This study was inductive quantitative using cross sectional design. Samples were students of class XII SMKN 1 Sedayu with 78 respondents. Sampling used simple random technique. Analyze used Kendal Tau. Kendal Tau analysis showed significant relationship between role of parents with pre-marital behavior in SMKN 1 Sedayu with p=0.000 (p<0.05) with the relationship weak r=0.399. In conclusion, there was a significant relationship between the roles of parents with pre-marital sexual behavior of adolescent in SMKN 1 Sedayu.